Composites of conducting polymers and nanoparticles for thin-film-multilayers OLEDs, OSCs and gas sensors - Dinh, Nguyen Nang (Communications in Physics, 2025)
In this work is a general view on nanostructured polymeric composite materials used for preparation and characterization of a group of organic optoelectronic devices, such as Organic Light-Emitting Diodes (OLEDs), Solar Cells (OSCs) and Gas Sensors (OGSs). From recent references, this work gives informations on structural, morphological, electrical and optical properties as well as perfomance behaviour of the nanocomposite devies. The analyzed data have demonstrated that nanostructured composite materials consisting of conducting polymers (CP) and nanoparticles have significantly contributed to enhance both the performance parameters and working time of devices. The presence of inorganic nanoparticles in polymers has strongly influenced all physical properties of the polymers. In this work we concentrated to analyze the most interesting properties of the OLEDs, OSCs and OGSs, such as electro-luminescence, photo-electrical conversion, and gas sensing. This review work also shows in general, the discovery source of the CPs, some typical CPs and their composites used for the fabrication of nanocomposite devices which aim at different practical purposes.